Chronic abdominal pain and persistent disorder of nutritional status - V. T. Ivashkin; Ye. A. Poluyektova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To show difficulties of differential diagnostics and prescription of adequate treatment in patient with abdominal pain and nutritional disorders.The main contents. Patient C., female, 58 years old, admitted the clinic in the spring of 2008. Symptoms included epigastric pain, sometimes belt-like, not related to food intake, posture or defecation, sensation of bitter taste, fever up to 37,2–37,4 °С without relation to time of day, physical activity or pain intensity. Symptoms started in childhood, onset of disease patient associated to irregular and improper nutrition. From 18-years of age almost permanently receives conservative treatment for abdominal pain, underwent three surgical operation without definite indications (cholecystectomy, Roux stomach resection, Bilroth I stomach resection). Conservative and surgical treatment did not result in pain relief. At examination presence of nutritional insufficiency draw attention. BMI was 15 kg/m2. The aim of investigation was to define the cause of abdominal pain, and to determine treatment approach. According to the results of investigation in the patient with tesselated personality disorder somatoform disorder was diagnosed (generalized somatoform pain). Treatment included drug therapy along with repeated conversations with the patient, that resulted in relative stabilization of her state.Conclusion. Estimating presented clinical case it is possible to draw conclusion on involvement of various departments of nervous system, including emotional component into the mechanism of abdominal pain. Thus, the key moment in investigation of the patient presenting complaints of pain, besides laboratory and instrumental tests is careful analysis of symptoms, past history and family history. The choice of an agent for treatment abdominal pain depends on the level of its generation.